1996
DOI: 10.1258/0956462961917410
|View full text |Cite
|
Sign up to set email alerts
|

Venous thrombosis in HIV infection

Abstract: Previous reports indicate that venous thrombosis is an infrequent problem in patients with HIV infection. Despite this, various HIV-related factors have been proposed as potentially thrombogenic and an HIV-related hypercoagulability has been suggested. At the present time, there exists no consensus of opinion regarding prophylaxis against venous thrombosis for hospitalized patients with HIV. This article aims to provide an overview of venous thrombosis in HIV infection with particular reference to published an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Our study showed a trend towards a higher risk of VTE with a low CD4 count (o200 cells/mL), although the association was not statistically significant. IDU has been identified as a strong risk factor for community-acquired VTE in young adults [48,49], mainly because of the venous damage induced by the drug abuse [12,16,22]. IDU accounts for nearly 10% of all communityacquired VTE and almost 50% of episodes in patients aged 40 years [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed a trend towards a higher risk of VTE with a low CD4 count (o200 cells/mL), although the association was not statistically significant. IDU has been identified as a strong risk factor for community-acquired VTE in young adults [48,49], mainly because of the venous damage induced by the drug abuse [12,16,22]. IDU accounts for nearly 10% of all communityacquired VTE and almost 50% of episodes in patients aged 40 years [48].…”
Section: Discussionmentioning
confidence: 99%
“…Studies mainly from the pre-HAART era estimated that the overall risk of VTE in patients with HIV infection was roughly 2-10-fold higher than expected in the general population [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, many studies were limited by small sample size [15,16,22,23] and a lack of a population-based comparison cohort [11][12][13]15,16,19,[21][22][23].AIDS-related opportunistic infections, neoplasms and HIV infection per se have been hypothesized to predispose patients to a hypercoagulable state [16]. Various other abnormalities in the haemostatic pathways of HIV-infected patients have also been reported [25][26][27].…”
mentioning
confidence: 99%
“…Thrombotic events of unexplained etiology have been well-documented in HIV-infected patients [10][11][12]. A hypercoagulable state as a result of anticardiolipin antibodies and protein S deficiency, a higher frequency of cytomegalovirus infection in an HIV setting with a propensity of cytomegalovirus to cause intimal proliferation as well as drug therapy, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There was, however, no beneficial effect of prophylaxis on mortality due to thromboembolic complications [48]. In chronic viral diseases, such as CMV or HIV infection, the risk of thromboembolic complications is relatively low [49,50].…”
Section: Clinical Aspects Of Hemostasis In Bacterial and Viral Infectmentioning
confidence: 99%